Design and development of a low cost technique for sorting household wastes using eddy current separation process. Issue 2 (3rd March 2016) - Amir, Merahi; Karim, Medles; Bendaha Mourad, Bardadi; Amar, Tilmatine
Abstract : Recovery and recycling of metals from wastes have a major role in the global economy because of the scarcity of raw materials and the problem of environmental pollution. This paper reports a technical and economic study for the development of a low-cost eddy-current separator for household waste treatment. Waste treatment in African countries suffers a developmental delay owing to the cost of such equipment. On the basis of preliminary results obtained by numerical simulation of the physical phenomena, in order to test several possible configurations, a prototype device has been built and tested. The experimental results obtained have led to an optimal configuration in terms of separation efficiency. Thus, a second more efficient device has been successfully developed and tested. The economic analysis revealed the benefit of local manufacture for such a separator.